Bilder für den Himmel : Kunstdrachen. - von Bismarck, Klaus; Krempel, Ulrich; Schmalenbach, Werner; Titus-Carmel, Gérard (Osaka : Goethe-Institut Osaka, 1989)
Antes, Horst ; Appel, Karel ; Arman ; Asano, Yae ; AY-O ; Bach, Elvira ; Bak, Imre ; Ben ; Brown, James ; Bruskin, Grisha ; Bulatow, Erik ; Buren, Daniel ; Buthe, Michael ; Ceccobelli, Bruno ; Cobo, Chema ; Dean, Graham ; Dibbets, Jan ; Domoto, Hisao ; Fiebig, Eberhard ; Flanagan, Barry ; Francis, Sam ; Fujie, Tami ; Geiger, Rupprecht ; General Idea ; Girke, Raimund ; Goldstein, Zvi ; Götz, K.O. (Karl Otto) ; Graubner, Gotthard ; De Guimaraes, José ; Hajek, Otto Herbert ; Hara, Takeshi ; Hoehme, Gerhard ; Hundertwasser ; Imaï, Toshimitsu ; Imamura, Yukio ; Inoue, Bukichi ; Janssen, Horst ; Kabakov, Ilya ; Kaks, Olle ; Kano, Mitsuo ; Kirkeby, Per ; Kitayama, Yoshio ; Kopystiansky, Igor ; Kurosaki, Akira ; Kusama Yayoi ; Kushner, Robert ; Kuwayama, Tadaaki ; Lee U-Fan ; Lenk, Thomas ; Liticevskij, Georgij ; Lohse, Richard Paul ; Matsuo, Ryusho ; Momose, Hisashi ; Motonaga, Sadamasa ; Nash, David ; Onoda, Minoru ; Paeffgen, C.O. ; Paladino, Mimmo ; Panamarenko ; Pfahler, Georg Karl ; Piene, Otto ; Rabuzin, Ivan ; Rauschenberg, Robert ; Richter, Gerhard ; Rissa ; Rosenbach, Ulrike ; de Saint-Phalle, Niki ; Salomé ; Scharf, Kenny ; Schultze, Bernard ; Schumacher, Emil ; Shingu, Susumu ; Shinohara, Ushio ; Shiraga, Kazuo ; Shoji, Satoru ; Smith, Leon Polk ; Sonderborg, K.R.H. ; Staeck, Klaus ; Stankowski, Anton ; Stella, Frank ; Sugai, Kumi ; Takahashi, Shu ; Tanaka, Atsuko ; Tatafiore, Ernesto ; Tinguely, Jean ; Titus-Carmel, Gérard ; Uecker, Günther ; Uematsu, Keiji ; Usami, Keiji ; Vasarely, Victor ; Vedova, Emilio ; Verhoef, Toon ; Walther, Franz Erhard ; Watanabe, Toyoshige ; Wawrin, Isolde ; Wesselmann, Tom ; Wunderlich, Paul ; Yokoo, Tadanori ; Yoshizawa, Mika
Duits & Japans
Bilder für den Himmel : Kunstdrachen, Goethe-Institut, Osaka, 16.04.1988 - 04.06.1988
boek